International Trade and Economic Growth: A Panel Data Analysis of Some Selected Sub-Saharan African Countries - Muhammad, Mua'zu Yusuf; Gujiya, Amina Aliyu (NIU Journal of Social Sciences, 2019)
This paper is to empirically evaluate the impact of international trade on economic growth in some selected Sub-Sahara African countries spanning from 2010 to 2017 using panel data obtained from World Bank (World Economic Indicators). The research used GDP as proxy for economic growth and the dependent variable whereas trade balance (proxy for international trade), money supply and CPI (proxy for inflation) are explanatory variables. Pooled Regression, fixed effect and random effect Analysis as well as Estimated Generalized Least Square Regression Analysis were employed for data analysis. The findings of the research shows that trade balance and CPI are positive but not significant in the three regressions and Estimated Generalized Least Square Regression. Money supply is negative significant under both pooled regression and Estimated Generalized Least Square Regression, but positively and negative but statistically not significant under fixed effect and random effect respectively. Therefore, the research recommends that Sub-Sahara African countries should pursue export promotion and import substitution with the sincerity of purpose. The monetary policies that will manipulate money supply to level of capable economy growth and avoid inflationary pressure should be adopted. Keyword: International Trade, Economic Growth, Estimated Generalized Least Square